Literary promotion as an extension activity facing Covid-19 (Cuadernos de Extensión Universitaria de la UNLPam, 2023)
The university extension process encompasses various modalities as a substantive process of hi-gher education, within which students with literary concerns are served, included in the Movement of Amateur Artists that exists in Cuban universities. It is a task that includes teaching and research and has an impact on the comprehensive training of university students. This article shows the results in the promotion of creative writing of the members of the Pablo Neruda Literary Creation Workshop, but also the changes that occur in the various actors involved in said task. Among the actions, the writing and debate of significant works stand out, collective readings, books presentation, elaboration and visualization of promotional videos stand out, while the knowledge, skills or experiences acquired are applied, which enriches the spiritual world of those who live in the community university and contributes to the advancement of cultural life, despite the Covid-19 pandemic.
Keywords: extension; literary creation; amateurs; Covid-19